PENGARUH BENTUK DAN BERAT DALAM PERANCANGAN KAPAL BARANG CEPAT - Julianto Sasono, Eko (Vocational School Diponegoro University, 2010)
Eko Julianto Sasono, in this paper explain that cargo ship express represent the ship type developed andchecked by Japan government in order to overcoming transportation problems by transport service in the land.Cargo ship express developed in two form, that is type of TSL-F and TSL-A. Determination form and ship weightexpress this very having an in with of speed and load capacity, in the plan laboured by a cargo ship express own thebig cargo hold and light machine.Keywords : Cargo ship express, load capacity, speed.